(untitled) (Latakia University Journal -Basic Sciences Series, 2025)
The geochemical characteristics and hydrocarbon generating potential of two source rock formations in the Northern Hussein Block of the Aleppo plateau/Syria; the Kermav formation (Paleocene) and the Jaddala formation (Eocene), were evaluated using the techniques of both prospecting geochemistry (a set of redox-sensitive trace elements signatures) and the Rock-Eval pyrolysis. The organic matter in the Kermav rocks is a type II Kerogen with a very good organic carbon content (TOC) and a very good generating potential, deposited under reduced conditions with fluctuations toward minor oxygen content according to the trace elements signature, indicating a marine depositional environment with varying levels of oxygen deficiency and a marine source of organic matter. In contrast, the TOC of Jaddala formation is lower than that of Kermav, but is good with good generating potential and shows relatively less maturity. It belongs to mixed type II/III kerogen that was deposited under more anoxic conditions with an important contribution of terrestrial organic matter, most likely in a marine depositional environment similar to that of Kermav with dilution of organic matter due to increasing mineral inputs. Both the organic matter and the rock component of the source rocks share a common origin according to trace elements data, that is, they were deposited simultaneously and the organic matter was not post-sedimentary or transported. The Jaddala formation showed signs of hydrocarbon migration from the other rock formations, eventually migrating from the kermav (specifically). Overall, the study provides insights into the geochemical characteristics, paleoenvironmental conditions, and hydrocarbon generation potential of both the kermav and Jaddala formations.